Chinese comprehenders’ interpretation of underinformativeness in L1 and L2 accented speech narratives - Li, Yanrui; Feng, Shuo (Frontiers in Psychology, 2023)
Second language (L2) speakers with foreign accents are well-known to face disadvantages in terms of language processing; however, recent research has demonstrated possible social benefits for foreign-accented L2 speakers. While previous research has focused on the ways in which first language (L1) speakers of English comprehend L2 speech, the present article contributes to this line of research by exploring the ways in which comprehenders from a different culture and linguistic background perceive L2 speech narratives. This study investigates this issue by exploring how comprehenders with Mandarin Chinese as the first language interpret underinformative utterances containing scalar and ad hoc implicature in L1, accent-free L2, and foreign-accented L2 speech narratives. The sentence judgment task with a guise design used written sentences rather oral utterances as stimuli in order to isolate the role of intelligibility factors. The results indicate that foreign accent confers social benefits on L2 speakers in that their omission of information in communication is tolerated and they are viewed as more likely to possess positive attributes. More importantly, we find that the bilingual characteristics of Chinese participants, as well as the different linguistic complexity of deriving scalar and ad hoc implicature, affect Chinese participants’ explanations of underinformative sentences of L2 speakers. This study contributes to our understanding of L2 language processing.